Say my name: name-based microaggressions as a function of white cultural hegemony in South African educational contexts - Head, Seannah; Dlamini, Sipho (Frontiers in Education, 2025)
In most African societies, particularly among Black people, names are central to people’s identity and are central to how young people develop a sense of self. In the post-colonial-apartheid context of South Africa, which we argue is largely governed by white cultural hegemony, the occurrence of varying subtle forms of racism is inevitable. Name-based microaggressions are one defining feature of the post-colonial-apartheid white cultural hegemonic context, specifically within educational contexts. In this article, we illustrate how white cultural hegemony gives rise to name-based microaggressions, perpetuated towards Black youth in the South African educational context, mostly by educators. We conducted eight (8) semi-structured interviews with Black youths based in a South African university, who had experiences of name-based microaggressions. The interviews were analysed using Thematic Analysis, yielding three (3) themes: name mispronunciations and Black names as an inconvenience, name-based microaggressions in the educational context, and the effects of name-based microaggressions. We conclude by showing how name-based microaggressions can have deleterious effects on the identity development of youths who are victims, affecting the ways in which they view themselves in relation to their culture, as well as the relationship they have with peers and educators. This article highlights the need for inclusive educational environments that honour students’ identities to avoid the perpetuation of racism in the educational context, and the associated effects of the occurrence of name-based microaggressions within the education space.